Valensinformasjon i NorKompLeks - Nordgård, Torbjørn (Nordiske Studier i Leksikografi, 2001)
This article addresses how valency (or argument structure) information is described in the NorKompLeks lexicon for Norwegian. We discuss the relation between modem syntactic theories and a practical description of all verbs and their valency properties in a language. We conclude that the lexical description could use an intuitive notion of constructions in order to cover the relevant properties of the verbs, and linguistic theories should be able to interpret these lexical properties. A number of examples from the material are discussed. The relevance for lexicography is that dictionaries could use simplified versions of the valency information, or that alternative publication formats will make it possible to include such information in future dictionaries.